Defeat of the urinary system against the background of connective tissue dysplasia in a 7-year-old child (clinical observation) - T. I. Bikmetov; I. V. Zorin; R. A. Zorina; E. V. Nesterenko (Лечащий Врач, 2024)
Background. Connective tissue dysplasia — impaired development of connective tissue in the embryonic and postnatal periods, a genetically determined condition characterized by defects in fibrous structures and the basic substance of connective tissue, leading to a disorder of homeostasis at the tissue, organ and organizational levels in the form of various morphofunctional disorders of visceral and locomotor organs with a progressive course, determining the features of associated pathology, as well as pharmacokinetics and pharmacodynamics of drugs. Due to the ubiquitous presence of connective tissue in the body, its changes are widespread, which leads to a variety of clinical manifestations affecting all organs and systems. The comprehensive spread of connective tissue in the body determines the multiple organicity of lesions in connective tissue dysplasia syndrome. Connective tissue dysplasia syndrome is quite often combined with pathology of the organs of the urinary system. Special attention is paid to the problems of nephrology in children in pediatrics. Early detection of a real lesion in children with connective tissue dysplasia is difficult. Early diagnosis of possible renal complications in DST in children has become a very relevant issue in the modern world. The study of the features of the course of kidney pathology against the background of connective tissue dysplasia in children is necessary to identify a group of patients at high risk for the formation and progression of nephropathies.Objective. The aim of the study was to present a clinical case of urinary system lesion against the background of connective tissue dysplasia in a 7-year-old child.Materials and methods. Patient O., born in 2016, was examined at the State Medical Institution "CSTO". During the examination of the child, the clinical and genealogical method, functional research methods (ultrasound examination of the abdominal cavity and retroperitoneal space, electrocardiography, daily monitoring of blood pressure), clinical and biochemical examination of blood and urine were used. Conclusion. The problem of kidney damage in connective tissue dysplasia is relevant in nephrological practice. Thus, early diagnosis of kidney damage in connective tissue dysplasia and their timely correction are necessary to prevent the formation and progression of chronic kidney disease.